AUDIT DELAY DAN FAKTOR PENYEBABNYA (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI) - Karsiati Karsiati (AKSES: Jurnal Ekonomi dan Bisnis, 2014)
The submission of financial statements has been set in the capital market. Undang-Undang No. 8 of 1995 on "Peraturan Pasar Modal" or Capital Market Regulation states that all listed companies in the stock market shall submit regular financial reports to BAPEPAM and announce to public. The timeliness of publishing the audited financial statements is very important, especially for companies - public companies who use capital market as a source of funding.The time length of audit completion by the auditor over the time difference financial reporting date to the date of the audit opinion on the financial statement is called the audit delay. However, the auditor may extend the period of the audit by delaying the completion of the audit, the financial statements due to certain reasons, such as to improve the quality compliance audit by an auditor who ultimately require more time.Several factors need to be considered to ensure timely publication of financial statements include: the size of the company, the level of corporate profitability, solvency, profit or loss experienced by the company, the size of the auditor, the auditor's opinion, the presence of the auditor the results of the previous period . Keywords :    audit delay, company size, profitability, solvency, the size of the auditor, the auditor's opinion.